SISTEM PENGENDALIAN INTERNAL PEMBIAYAAN MURABAHAH PT BPR SYARIAH PADA MASA PANDEMI COVID-19 - Saifudin Saifudin; Aprih Santoso; Ardiani Ika Sulistyawati; Nurul Khamim (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
This research was conducted at the head office of PT BPRS Bina Finansia in the marketing and remedial segment. The reason for this research is to analyze the internal control system of murabahah financing in 2018-2020. This study uses qualitative methods,by using triangulation of methods and data sources, these are observation, interviews and documentation. Informant research is based on the principles of appropriateness and adequacy, there are 8 people in this research of basic informant’s principle. The results of this reasearch lead that internal control system towards financing of murabahah at PT BPRS Bina Finansia is still not working out in a good way. Lack of control to collect murabahah financing administration and lack of client charging become a factor of bad debs occur, causing an increase problem of financing